7-S CHALLENGES IN PUBLIC SECTOR RISK MANAGEMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper examines the problems and peculiarities of risk management in the public sector in Bulgaria. Several discussion questions raised: To what extent do public sector administrations have an adequate and working toolkit for risk management? Is the existence of formal tools enough to meet modern challenges? Is there a sufficiently developed organizational culture and knowledge of risk management in the public sector? How does risk management affect network collaboration? How does digital transformation impact the innovation process in the public sector? Can government organizations take the risk of digital transformation? The solution to these questions depends not only on how the evaluation framework will be built, but also on what the design of the risk management system should be, the commitments of the administration to monitor and control it, and the organizational culture and management style. The purpose of the paper is to point out the main deficits in risk management in the Bulgarian public sector from different perspectives and to summarise them in a holistic model - McKinsey's 7-S framework. Data from secondary analyzes of the state of the Bulgarian administration were used, which were triangulated with findings from an empirical study conducted by the authors. The conclusions are that problems are observed in all elements of the risk management framework, although progress is observed over time. From a perspective of the direction of improving the efficiency of the process, the possibility of transferring methodologies and practices to agile risk management is considered. The authors support the view that as an approach, it can solve many of the shortcomings of the traditional bureaucratic model and positively impact network collaboration in the context of digital transformation.